Pink Hibiscus Mealybug, Maconellicoccus hirsutu (Green) - M.A. Hoy; A. Hamon; R. Nguyen (EDIS, 2002)
This document provides an in-depth profile of the pink hibiscus mealybug, Maconellicoccus hirsutus, a serious pest affecting various plants in tropical and subtropical regions. It details the pest's introduction to Florida, its potential impact on crops and ornamental plants, and the increased pesticide use required for management. The article also discusses the mealybug's distribution, life cycle, and damage caused to plants. Additionally, it explores biological control methods, including the use of natural enemies like ladybugs and parasitoids to suppress mealybug populations.